Factors Influencing Male Participation in Maternal Health Care among Married Couples in Nepal: A Population-based Cross-sectional Study - Sharma, S.; Aryal, U. R.; Shrestha, A. (Kathmandu University Medical Journal, 2020)
Background The male involvement in maternal health care is essential to reduce obstetric complications. However, there is little known about factors contributing to male participation in maternal health in Nepal. Objective To assess predisposing, enabling and reinforcing factors contributing male participation in maternal health care in Nepal. Method A population based cross-sectional study was conducted among 374 married couples. Ethical approval was obtained from Institutional Review Board of Kathmandu Medical College Teaching Hospital. The data was collected, using modified Safe Motherhood and Partnership Family Approach Model. Multivariable logistic regression was applied to account associated paternal factors. Concentration curve and concentration index were computed to measure equity gap between lowest and highest quintiles. Result While four out of ten husbands reported high level of their involvement in maternal health care practices, wives reported relatively less involvement of their husbands. Logistic regression showed that husband having low family income, knows about immunization, contact with family planning providers were more likely to participate. In contrary, according to wives, husbands’ who have ever been to health facility, discuss family planning with others, contact with family planning providers and who knows about exclusive breast feeding were less likely to participate. The study also showed that socio-economic factors play a significant role. Conclusion Male involvement in maternal health care practices is low. Predisposing, enabling and reinforcing factors play a significant role; however, some contradictions among husbands’ and wives’ perspectives provide strong evidence on significance of communication within partners on maternal health care issues.